THE PROTECTIVE ROLE OF Moringa oleifera IN REPRODUCTIVE TRAITS OF CADMIUM CHLORIDE EXPOSED JAPANESE QUAILS - Aqeel Ur Rehman; Zahid Farooq; Irfan Baboo; Haseeb Khaliq (Journal of Animal and Plant Sciences, 2025)
ABSTRACT This study evaluates the impact of cadmium chloride (CdCl₂) exposure on breeding Productivity and the potential mitigating role of Moringa oleifera as an antioxidant agent in Japanese quail (Coturnix japonica). The experimental design followed a completely randomized design (CRD) with 400 day-old Japanese quail, divided into eight treatment groups: NC (negative control), PC (positive control fed with Moringa oleifera), T1 (Cd 25 mg/kg), T2 (Cd 50 mg/kg), T3 (Cd 75 mg/kg), T4 (Cd 25 mg/kg + Moringa), T5 (Cd 50 mg/kg + Moringa), and T6 (Cd 75 mg/kg + Moringa). Production and breeding productivity were assessed through body weight, hen-housed egg production (HHEP), hen-day egg production (HDEP), egg weight, egg mass, fertility, hatchability, and key egg quality parameters from the month of November 2023 to April 2024 at 24th week. Results indicated that Cd exposure significantly impaired breeding productivity and egg quality (p ≤ 0.01), with the highest Cd level (75 mg/kg) causing the most severe declines. Conversely, groups supplemented with Moringa oleifera demonstrated significant improvements (p ≤ 0.01) in body weight, egg production, egg mass, fertility, and hatchability, highlighting Moringa’s protective antioxidant effects. ANOVA analysis confirmed significant differences among groups, reinforcing the effectiveness of Moringa oleifera supplementation at 7 g/kg feed in counteracting cadmium toxicity in quail. These findings suggest Moringa as a viable dietary intervention for improving poultry health under heavy metal contamination.
Keywords: Cadmium chloride; Moringa oleifera; productive performance; egg quality; Japanese quail